Characterization Of Intestinal Microbiota In Celiac Children - Lahcene, F.; Tir Touil Meddah, A.; Bouziane-nedjadi, K.; Meddah, B.; Leke, A. (University of Eloued جامعة الوادي, 2016)
Celiac disease (CD) is enteropathy autoimmune induced by the ingestion of gluten in genetically predisposed subjects. The ingestion of gluten is responsible for the symptoms of CD, and a disturber of the intestinal microbiota. In this study, 13 Samples of intestinal biopsy, 15 fecal samples from celiac children, and 10 from controls children respectively were collected and analyzed by conventional culture technique to characterize the microbial profile intestinal of celiac children. There was 24 celiac children (8 boys), Mean age at diagnosis was 9.52 years, all have clinical manifestations, positive anti-transglutaminase antibodies and mucosal lesions suggestive of CD (Marsh Classification).We found a difference in intestinal microbiota, between celiac and controls children for example the Enterobacteria, Clostridium sp and Staphylococcus sp were remarkably higher in biopsy and fecal samples of celiac children than in controls. Inversely the Enterococcus sp, Lactobacillus sp and Clostridium sp were slightly lower in celiac children. Our results indicate an imbalance in intestinal microbiota for celiac children as reduction in the numbers of Lactobacillus sp, Enterococcus sp and increases in the numbers of Enterobacteria, Staphylococcus sp and Clostridium sp.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: Celiac disease, Intestinal Microbiota, Anti-transglutaminase, Lacobacillus sp